Poverty Alleviation through Social Entrepreneur - Yusriadi Yusriadi; Saidna Zulfiqar bin Tahir; M. Awaluddin; Misnawati Misnawati (Mahesa Research Center, 2020)
This research was conducted to determine the application of social entrepreneurship; this will be one solution to revive the country's economy, especially the business sector, which has had a huge impact due to the COVID-19 pandemic. The number of informants in this study was 10 mothers who received assistance from the Family Hope Program (PKH). The data in this study were obtained from the results of observation, interviews, and documentation. The results of the study describe the existence of social entrepreneurs that were carried out on PKH beneficiary mothers who have given positive results to revive business groups in Indonesia which have an impact on COVID-19, especially which will contribute to the surrounding community for transformation by seeing business opportunities carried out with a social spirit in this era of COVID-19. Social entrepreneurs who are carried out through mentoring have opened new businesses in the economy, which will add to the heterogeneity of entrepreneurs in Indonesia